Compensatory measures in technological disasters: a neglected link? - Dowbor, Monika; Resende, Roberta Carnelos; Ruscheinsky, Aloísio (Ciências sociais UNISINOS, 2024)
The objective of this research is to analyze how the medium-term effects of disasters in Brazil are mitigated. To this end, an analysis of the legislation and the Terms of Adjustment of Conduct was used, the instrument through which disaster-causing companies and the Brazilian State adapt conducts, in four specific cases (Chevron, Iberpar, Samarco and Hydro Alumnorte). We detected the predominance of the generalist and vague definition of both compensatory measures and the instruments and strategies for their implementation, but with some learning over time. The exclusion of the participation of the affected communities as a recurring aspect in the original agreements and the absence of specialized sectors of the State both in the control and in the implementation of the actions draws attention. O objetivo desta pesquisa é analisar como são mitigados os efeitos de médio prazo decorridos de desastres no Brasil. Para tanto, recorreu-se à análise da legislação e dos Termos de Ajuste de Conduta, instrumento por meio dos quais as empresas causadoras de desastres e o Estado brasileiro adequam condutas, em quatro casos específicos (Chevron, Iberpar, Samarco e Hydro Alumnorte). Detectamos o predomínio da definição generalista e vaga tanto das medidas compensatórias quanto dos instrumentos e estratégias de sua implementação, mas com certa aprendizagem ao longo do tempo. Chama atenção a exclusão da participação das comunidades atingidas como aspecto recorrente nos acordos originais e a ausência dos setores especializados do Estado tanto no controle como na implementação das ações.